Interpretation – musical reproduction – theory of performance: bringing together the elements for a conceptual reform of the interpretative and the performance practice as a scholar discipline (Per Musi, 2012)
Great difficulties are noted in human sciences regarding the definition and use of the concepts designating cultural phenomena. The main objective is to demonstrate how these concepts differ in sense and end. The next step consists in a careful analysis of the concept of musical reproduction. Finally, the trinomial reproduction, interpretation and musical performance is proposed as a conceptual basis for teaching and research of the musical interpretative practice. At the same time, the theoretical field of the discipline increases in its scope, migrating from a basically interpretative concept to that of a multiform artistic process with great productive and transformational potential that also includes the extramusical elements of reproduction.